2021
DOI: 10.1186/s12872-021-02307-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide prevents arterial medial calcification in rats with diabetic nephropathy

Abstract: Background Arterial medial calcification (AMC) is associated with a high incidence of cardiovascular risk in patients with type 2 diabetes and chronic kidney disease. Here, we tested whether hydrogen sulfide (H2S) can prevent AMC in rats with diabetic nephropathy (DN). Methods DN was induced by a single injection of streptozotocin and high-fat diet (45% kcal as fat) containing 0.75% adenine in Sprague–Dawley rats for 8 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
(60 reference statements)
0
8
0
2
Order By: Relevance
“…Additionally, previous studies found that H 2 S inhibited the activation of fibrosis-related cells and cytokine expression, then alleviated renal fibrosis, and improved renal function in the rats with renal sclerosis caused by renal tubular epithelial mesenchymal transition (EMT) [ 18 ]. Exogenous H 2 S significantly decreased the level of TGF- β 1 in vivo , increased the expression of aortic elastin, and prevented diabetic nephropathy arteriosclerosis in rats [ 19 ]. H 2 S improved myocardial fibrosis via suppressing the TGF- β 1 /Smad signaling pathway [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies found that H 2 S inhibited the activation of fibrosis-related cells and cytokine expression, then alleviated renal fibrosis, and improved renal function in the rats with renal sclerosis caused by renal tubular epithelial mesenchymal transition (EMT) [ 18 ]. Exogenous H 2 S significantly decreased the level of TGF- β 1 in vivo , increased the expression of aortic elastin, and prevented diabetic nephropathy arteriosclerosis in rats [ 19 ]. H 2 S improved myocardial fibrosis via suppressing the TGF- β 1 /Smad signaling pathway [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S, as an important mediator in numerous physiological processes, has the effects of antioxidation, anti-inflammation, antiapoptosis, cytoprotection, and pro-angiogenesis. Exogenous H 2 S supplementation can alleviate the occurrence of vascular calcification by maintaining the contractile phenotype of HUASMCs and inhibiting the osteogenic phenotype differentiation of HUASMCs. , Moreover, H 2 S can inhibit the absorption of phosphate by inhibiting the expression of Pit-1 on the membrane of HUASMCs, and play an antiarterial calcification effect via scavenging oxides to combat oxidative stress. It is inferred that PLCL/KS//PLCL/SH-Cu mats released H 2 S under the trigger of GSH to reduce intracellular and extracellular calcium deposition and inhibit the expression of genes involved in the HUASMCs osteogenic transformation to alleviate arterial calcification.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, this process significantly impacts the advancement of hypertension [ 88 , 89 ]. Numerous experimental studies conducted in vivo and in vitro have provided evidence that H 2 S can upregulate elastin levels by inhibiting Stat3/CatS signaling, and can prevent elastin loss and degradation, thereby stabilizing HASMCs as contractile VSMCs (Marker: SM α-actin and SM22α) and decreasing vascular calcification [ 90 , 91 ].…”
Section: Cats Are Involved In All Phases Of Stent-related Restenosismentioning
confidence: 99%